Lymphocytic thyroiditis: a correlation of cytological grades with clinical, biochemical and ultrasound findings - Uma, P.; Kartheek, B.V.S.; Himaja, S.; Lekha, J. Chandra; Babu, A. Kasi; Lakshmi, A. Bhagya (International Journal of Research in Medical Sciences, 2017)
Background: Hashimoto’s thyroiditis sometimes referred to as goitrous thyroiditis is a synonym of chronic lymphocytic thyroiditis or autoimmune thyroiditis. Chronic lymphocytic thyroiditis (Hashimoto’s thyroiditis) is one of the most common cause of goiter and hypothyroidism, it is found most commonly in middle aged and young female, but can also occur in other age groups, including children. Chronic lymphocytic thyroiditis can be graded based on cytomorphology. In this study an attempt has been made to correlate the grades with clinical findings, biochemical levels and ultrasonography findings. Methods:This is a prospective study conducted on 309 patients in the Department of Pathology, Andhra Medical College, Visakhapatnam. The various parameters like patient’s clinical presentation, biochemical levels and thyroid ultrasound were studied. Fine needle aspiration of thyroid gland and grading of thyroiditis was done on smears. The grades were correlated with above parameters and the correlation indices were evaluated statistically. Chi-square tests were used for statistical correlation and p value of <0.05 was considered significant. Results: Most of the patients were females (297, 96.11%) who commonly presented with a diffuse goiter (263, 85.11%). Asymptomatic cases (193, 62.46%) and elevated TSH (194, 62.78%) were common. Most of the cases had grade I/II disease (299, 96.76%) by cytology. Conclusion:FNAC is a simple, safe and cost effective procedure and is a sensitive and specific diagnostic tool in diagnosing chronic lymphocytic thyroiditis. Cytological grading of chronic lymphocytic thyroiditis helps in assessing the severity of the disease and can predict the thyroid functional status. A combined approach of cytological grading of chronic lymphocytic thyroiditis along with ultrasonography and biochemical levels can detect subclinical hypothyroid states and provide a guide to therapy.